High-Dose vs. Low-Dose Proton Pump Inhibitors Post-Endoscopic hemostasis in patients with Bleeding Peptic Ulcer. A meta-analysis and meta-regression analysis - Sgourakis, George; Chatzidakis, George; Poulou, Androniki; Malliou, Panagiota; Argyropoulos, Theodoros; Ravanis, George; Vagia, Aphroditi; Kpogho, Itseoritse; Briki, Adam; Tsuruhara, Hana; et al. (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Present meta-analysis aims to evaluate studies of low- versus high-dose proton pump Inhibitors (PPI) post-endoscopic hemostasis, including the newly published randomized controlled trials (RCTs) and to conclude whether low-dose PPI can generate the comparable results as high-dose PPI. Materials and Methods: To identify suitable trials, the electronic databases PubMed, Medline, Cochrane Library, and the Embase were used. All RCTs concerning low- versus high-dose PPI administration post-endoscopic hemostasis published until December 2016 were identified. Primary outcomes were rebleeding rates, need for surgical intervention, and mortality. Results: Studies included a total of 1.651 participants. There were significantly less cases of rebleeding in the low-dose PPI treatment arm (p=0.003). All but one study provided data concerning need for Surgical Intervention and Mortality. The respective effect sizes were [odds ratio (OR), 95% confidence intervals (CI): 1.35, 0.72-2.53] and [OR, 95% CI: 1.20, 0.70-2.05]. Both treatment arms were comparable considering the aforementioned outcomes (p=0.35 and p=0.51, respectively). Meta-regression analysis likewise unveiled comparable outcomes between studies using pantoprazole versus lansoprazole concerning all three outcomes [rebleeding (p=0.944), surgical intervention (p=0.884), and mortality (p=0.961)]. Conclusion: A low-dose PPI treatment is equally effective as a high-dose PPI treatment following endoscopic arresting of bleeding. However, we anticipate the completion of more high-quality RCTs that will embrace distinct ethnicities, standardized endoscopic diagnosis and management, double-blind strategies, and appraisal of results working specific standards over clear-cut follow-up periods. Cite this article as: Sgourakis G, Chatzidakis G, Poulou A, et al. High-Dose vs. Low-Dose Proton Pump Inhibitors Post-Endoscopic Hemostasis in patients with Bleeding Peptic Ulcer. A meta-analysis and meta-regression analysis. Turk J Gastroenterol 2018; 29: 21-30.